Meta-analysis The Influence of the Flipped Classroom Model on Problem Solving Ability in Revolution 4.0 Era - Harso, Aloisius; Andi Yustira Lestari; Nadriyah; Andri Kurniawan; Hadi Widodo; Tomi Apra Santosa; Destra Amni (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to determine the effect of the flipped classroom model on the problem-solving ability of students in the industrial revolution era 4.0. This study is a type of meta-analysis research. Data sources come from 13 national and international journals published in 2021-20224. The inclusion criteria in this study are research derived from journals indexed by Sinta and Scopus, research related to the influence of the flipped classroom model on students' problem-solving abilities, tracing data sources from Researchgate, SciencedDirect, Mendeley, and ERIC, and research has complete data to calculate the value of effect size. Data analysis with the help of Microsof Excel and Jamovi applications. The results of this study concluded that the application of the flipped classroom model had a significant effect on students' problem-solving abilities with an average effect size value of 1.14 and Standard Error of 0.42. This finding has a positive impact on teachers to apply this flipped classroom model in developing students' problem-solving skills.